Lithium batteries : advanced technologies and applications - Scrosati, Bruno; Abraham, K. M.; Schalkwijk, Walter A. van; Hassoun, Jusef (Electrochemical Society series., 2013)
"With their use in everyday electronics and their increased use in industry applications, lithium ion batteries are an important source of power. Covering the most cutting-edge advances and technology in lithium ion batteries, Lithium Batteries teaches readers how to develop the most efficient advanced rechargeable batteries. This timely text covers various lithium ion devices, including lithium-air batteries aqueous, lithium-air polymer batteries, lithium-sulfur, and batteries for medical applications. The authors also review problems and alternatives to lithium ion batteries, including moderate temperature sodium batteries, magnesium batteries, and hybrid super-capacitors"--